Experimental Bothrops atrox Envenomation: Blood Plasma Proteome Effects after Local Tissue Damage and Perspectives on Thromboinflammation - Cavalcante, Joeliton S. [UNESP] (2022)
The clinical manifestations of Bothrops atrox envenoming involve local and systemic changes, among which edema requires substantial attention due to its ability to progress to compartmental syndromes and sometimes cause tissue loss and amputations. However, the impact of edema on the poisoned body’s system has not been explored. Thus, the present study aimed to explore the systemic pathological and inflammatory events that are altered by intraplantar injection of B. atrox venom in a mouse model through hematologic, lipidic, and shotgun proteomics analysis. Plasma samples collected showed a greater abundance of proteins related to complement, coagulation, lipid system, platelet and neutrophil degranulation, and pathways related to cell death and ischemic tolerance. Interestingly, some proteins, in particular, Prdx2 (peroxiredoxin 2), Hba (hemoglobin subunit alpha), and F9 (Factor IX), increased according to the amount of venom injected. Our findings support that B. atrox venom activates multiple blood systems that are involved in thromboinflammation, an observation that may have implications for the pathophysiological progression of envenomations. Furthermore, we report for the first time a potential role of Prdx2, Hba, and F9 as potential markers of the severity of edema/inflammation in mice caused by B. atrox.